ANALISIS MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BANK CENTRAL ASIA,Tbk CABANG BANDAR LAMPUNG - Ardansyah -; Paulus Hasan (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2014)
Job satisfaction and job motivation are directly related to staff performance. Job satisfactionand job motivation experienced by staff could reduce or increase staff performace. Staff who feelssatisfied with the job obtained will be motivated to increase his/her performace, consequently it willimpact on improving the company performance overall. This research was done at the Indonesiabased PT Bank BCA, Tbk . The aim of the research is to investigate the effect of staff performacerelation to the job satisfaction and job motivation. As independent variables are job satisfaction andjob motivation dependent variable is staff performance. The results of the analysis using moderatedregression are the job satisfaction variable and job motivation are positively influenced to jobsatisfaction